INTEGRATING SOCIAL MEDIA AND CONSUMER BEHAVIOR: AN ANALYSIS OF THE EFFECTS OF CONTENT, INFLUENCER CREDIBILITY, AND E-WOM ON PURCHASE INTENTION THROUGH BRAND ENGAGEMENT - Sri Asmirani; Farida Islamiah (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to examine the influence of social media content, influencer credibility, and electronic word of mouth (e-WOM) on consumers’ purchase intention, with brand engagement as a mediating variable. A quantitative, explanatory research design was applied, collecting data from 250 active Instagram users exposed to fashion-related promotional content. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The findings reveal that social media content, influencer credibility, and e-WOM have significant positive effects on both brand engagement and purchase intention, directly and indirectly. Brand engagement acts as a strong mediator linking digital marketing stimuli to consumer behavioral responses. Theoretically, this study reinforces the Stimulus–Organism–Response (S–O–R) framework in explaining digital consumer behavior, while practically, it highlights the importance of authentic content creation, credible influencer selection, and interactive communication management in enhancing consumer engagement and driving purchase intentions through social media platforms.